Assessment of the Educational Environment of Undergraduate Medical Education in Bangladesh (Bangladesh Journal of Medical Education, 2024)
Since the educational environment influences the academic outcomes of students, it is necessary to periodically measure it. This evaluation is based primarily on students' perceptions of the educational environment. The study aimed at measuring the educational environment of undergraduate medical education in Bangladesh, identifying problem areas, and suggesting ways for improvement. The DREEM inventory was used to conduct a cross-sectional survey of 255 medical undergraduates in different phases of their studies. The study revealed that the environment was 'more on the positive side' (score 108 out of 200). The mean score in the 'Students' Social Self-perception' subscale was 14, interpreted as 'not a nice place'. No significant difference was observed between perceptions of male and female undergraduates in different subscales. The study revealed that the fourth-year students perceived the atmosphere as worse than in other years. Out of the 50 total items, one had a mean score above 3, 36 had a mean score of 2-3, and 11 had a mean score of less than 2. Problematic areas have been identified and suggested remedies have been provided. The study has provided a comprehensive overview of undergraduate medical education's educational environment in Bangladesh and highlighted the areas requiring improvement.  BJME, Volume-15, Issue-02, July 2024: 60-70